2014
DOI: 10.1007/s10616-014-9727-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteome array identification of bioactive soluble proteins/peptides in Matrigel: relevance to stem cell responses

Abstract: Matrigel and similar commercial products are extracts of the Engelbreth-Holm-Swarm sarcoma that provide a basement-membrane-like attachment substrate or gel that is used to grow cells on or in, respectively. To ascertain further what proteins may be present in Matrigel, besides its major basement-membrane constituents, an analysis of the expressed liquid of gelled Matrigel was performed using proteome array technology. Among the growth factors/cytokines assayed, high positive detection was found for IGFBP1, IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 43 publications
1
56
0
Order By: Relevance
“…Certain laminin isoforms, fibronectin and collagen type-IV, are critical for the development of the neural crest [45]. NB cells migrate extensively in Matrigel, which contains these ECM molecules [27], which is in line with our findings.…”
Section: Matrigel Is the Preferred Substratum For Nb Invasionsupporting
confidence: 91%
“…Certain laminin isoforms, fibronectin and collagen type-IV, are critical for the development of the neural crest [45]. NB cells migrate extensively in Matrigel, which contains these ECM molecules [27], which is in line with our findings.…”
Section: Matrigel Is the Preferred Substratum For Nb Invasionsupporting
confidence: 91%
“…It has been shown that Matrigel contained various biologically active proteins, such as IGF1, TGFβ, EGF, bFGF, and PDGF, that could increase the frequency of tumor xenograft (20). Hence, to identify the stimuli, we selected 11 cytokines that were enriched in Matrigel (SI Appendix, Table S2) (20,21). These factors were divided into three groups according to their different bioactivities, such as promoting cell proliferation, stimulating angiogenesis, and regulating cell stemness, and administrated through tail i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Commercial Matrigel is widely used in human stem cell cultures by mimicking the extracellular matrix (ECM) [55], and it is known to contain components other than structural ECM proteins, such as growth factors and MMPs 2 and 9 [56], or even intracellular or membrane proteins [55]. Talbot et al [57] demonstrated by semi-quantitative analyses, with capture antibody arrays, the presence of various secreted or soluble proteins and peptides classified as growth factors, chemokines and other proteins with biological activity in four different lots from commercial Matrigel, including the Vascular Endothelial Growth Factor (VEGF), chemokine MCP-1 and peptide C5a. However, these results did not answer some questions about the biological activity of proteins or peptides present in Matrigel, which could impact experiments in vitro involving cell culture.…”
Section: Discussionmentioning
confidence: 99%